Effects of Two Dietary Lipid Sources at Two Levels on the Survival, Growth and Fatty Acid Composition of the Giant Freshwater Prawn, Macrobrachium rosenbergii - kim, Young Chul; Romano, Nicholas; Teoh, Chaiw Yee; Ng, Wing-Keong (Journal of Science and Technology, 2014)
A 10 week feeding trial was conducted to investigate dietary crude palm oil (CPO) or squid liver oil (SLO), at 3.5% (low) or 9.5% (high) as a 2 × 2 factorial design on survival, growth and whole body fatty acid composition of the giant freshwater prawn, Macrobrachium rosenbergii.  Growth performance was lowest and highest for prawns fed the CPO-low and SLO-high diets, respectively.  While prawns fed the CPO-high diet had lower growth than those fed the SLO-low diet, no significant differences were detected.  Significant interactions were found for oleic acid, arachidonic acid, n-6 polyunsaturated fatty acids (PUFA) and n-3/n-6 PUFA, while long chain PUFA, eicosapentaenoic acid and docosahexaenoic acid of the prawns were significantly lower when fed the CPO-based diets.  Lower growth of M. rosenbergii fed the CPO-based diets may be related to less favorable fatty acid ratios and/ or lowered digestibility but higher dietary CPO can help mitigate this.